Extreme Natural Hazards, Disaster Risks and Societal Implications - Ismail-Zadeh, Alik; Urrutia Fucugauchi, Jaime; Kijko, Andrzej; Takeuchi, Kuniyoshi; Zaliapin, Ilya (Cambridge : Cambridge University Press, 2014)
This book presents a unique, interdisciplinary approach to disaster risk research, combining cutting-edge natural science and social science methodologies. Bringing together leading scientists, policy makers and practitioners from around the world, it presents the risks of global hazards such as volcanoes, seismic events, landslides, hurricanes, precipitation floods and space weather, and provides real-world hazard case studies from Latin America, the Caribbean, Africa, the Middle East, Asia and the Pacific region. Avoiding complex mathematics, the authors provide insight into topics such as the vulnerability of society, disaster risk reduction policy, relations between disaster policy and climate change, adaptation to hazards, and (re)insurance approaches to extreme events. This is a key resource for academic researchers and graduate students in a wide range of disciplines linked to hazard and risk studies, including geophysics, volcanology, hydrology, atmospheric science, geomorphology, oceanography and remote sensing, and for professionals and policy makers working in disaster prevention and mitigation.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Natural disasters; Environmental disasters; Environmental risk assessment